Study of consolidation chemotherapy after definitive chemoradiation in locally advanced carcinoma esophagus in a tertiary care hospital - Ahmad, Wajahat; Najmi, Arshad Manzoor; Wani, Nahida; Wani, Shaqul Qamar; Banday, Saquib Zaffar; Nasreen, Shahida (ScienceRise: Medical Science, 2023)
Concurrent chemoradiation (CCRT) is considered the standard of care in locally advanced and inoperable carcinoma oesophagus patients. However, the majority of these patients have residual disease after completion of CCRT, and there are no definitive treatment guidelines for the management of the residual disease. Reports on consolidation chemotherapy for patients with oesophagal cancer after definitive CCRT are rare and have shown mixed results. The aim of this study was to see the effects of consolidation chemotherapy in patients of CCRT who had residual disease and were not surgical candidates and also monitor its side effects. Material and methods: It was a prospective interventional protocol over 2 years where patients received 4 cycles of consolidation chemotherapy post-CCRT. These patients were followed after completion of chemotherapy for response, toxicity and survival. Results: 45 patients were initially enrolled for the study, histopathologically proven carcinoma of the oesophagus, out of which 30 patients finally received the full course of treatment and were available for final assessment. After consolidation chemotherapy, 23 (76.7 %) patients had a complete response, 3 (10 %) had a partial response, and 4 (13.3 %) had stable disease. There was no progression of the disease during treatment. The overall treatment protocol was well tolerated by all the patients. There were no grade IV toxicities. On follow-up till the compilation of this data, 23 (76.6 %) of the patients were alive, and 7 (23.3 %) died (disease-related events). Out of these 7 patients, 4 patients had a local failure, and 3 patients developed distant metastasis in the form of brain and liver metastasis. Conclusion: Consolidation chemotherapy after concurrent chemoradiation in locally advanced, inoperable carcinoma oesophagus is a well-tolerable protocol with high chances of complete response rates